2019
DOI: 10.1108/ijwhm-02-2019-0021
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health in mental health services: a qualitative study

Abstract: Purpose The purpose of this paper is to explore occupational health (OH) clinicians’ perspectives on employee mental health in the mental health workplace in the English National Health Service. Design/methodology/approach Thematic analysis of data from seven semi-structured interviews is performed in this paper. Findings Three themes emerged under the core theme of “Situating OH services”: “the Uniqueness of the mental health service setting”, “the Limitations of OH services” and “the Meaning of mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Various studies have linked occupational stress in the food service industry to excessive workloads, lack of job control, and variable pay and schedules [ 13 , 14 , 15 ]. With mass layoffs and increased sense of insecurity among employees, several studies have shown that the pandemic is exacerbating these stressors [ 2 , 16 , 17 , 18 ]. Seventy-five percent of frontline workers reported that the pandemic has negatively impacted their mental health and as the economy slowly reopens, occupational stress among frontline workers in the restaurant industry continues to grow [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have linked occupational stress in the food service industry to excessive workloads, lack of job control, and variable pay and schedules [ 13 , 14 , 15 ]. With mass layoffs and increased sense of insecurity among employees, several studies have shown that the pandemic is exacerbating these stressors [ 2 , 16 , 17 , 18 ]. Seventy-five percent of frontline workers reported that the pandemic has negatively impacted their mental health and as the economy slowly reopens, occupational stress among frontline workers in the restaurant industry continues to grow [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%